Słownictwo strzeleckie w transmisjach telewizyjnych podczas Igrzysk Olimpijskich w Rio de Janeiro - Sobolewska, Monika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the following article I present description of jargon used by sports commentators reporting on sport shooting during 2016 Summer Olympic. Sport shooting is a niche discipline which is not very well known in our society. Each of 15 olympic competitons’ name is created according to certain rules. Moreover, an abrreviation for each discipline was created (for example: Ppn or Ksp). The task of journalists during Olympic Games is to present this event in such a way that each spectator will understand what is the idea behind it. Sports commentators deal profesionally with transmitting information about different disciplines during live streams. They have a very short time to prepare themselves for work that is why they have trouble with explaining sociolects of particular sport groups. Furthermore, it can lead to numerous mistakes, and vague hints. In the article I try to bring about idioms used by journalists, and I explain factual errors that result from misuderstanding of terms refering to particular discipline. I draw attention to the most common nouns, adjectives, and evaluative adverbs.